Highly-accessible, doped TiO2 nanoparticles embedded at the surface of SiO2 as photocatalysts for the degradation of pollutants under visible and UV radiation - Cani, Damiano; van der Waal, Jan C.; Pescarmona, Paolo P. (Applied catalysis. A, General, 2021)
[Display omitted] •Novel strategy to produce photocatalysts in which doped TiO2 nanoparticles are highly dispersed and firmly embedded at the surface of a SiO2 matrix.•Higher removal efficiency of probe pollutants compared to the benchmark P25 TiO2.•Highly-enhanced TON values in the degradation of rhodamine B and phenol under visible radiation. A series of photocatalysts consisting of C- and N-doped titanium dioxide (TiO2) nanoparticles highly dispersed and firmly embedded at the surface of a silica matrix were prepared using a novel synthesis method in which activated carbon has a double role: it acts as support for depositing the TiO2 nanoparticles and as hard template for generating a silica matrix that embeds them. Additionally, the use of activated carbon in combination with ammonia during the synthesis led to carbon and nitrogen doping of the TiO2 domains, which enhanced their absorption of radiation in the visible range. The combination of these features led to higher activity (i.e. higher removal % and TON) in the photocatalytic degradation of probe pollutants (phenol and rhodamine B) compared to the benchmark P25 TiO2 under UV and, even more markedly, under visible radiation. Particularly, the photocatalyst prepared with 10 wt% of TiO2 nanoparticles (10%TiO2NP@SiO2) displayed much enhanced TON values under visible radiation compared to P25 TiO2 (a 12 times higher TON with rhodamine B, and an 8 times higher TON with phenol). The TON values are also significantly higher compared to any previously reported TiO2-SiO2 photocatalyst. The TiO2NP@SiO2 photocatalysts can be effectively reused in consecutive runs. The photocatalytic activity of the prepared materials was correlated to their physicochemical properties by means of a thorough characterisation using a combination of techniques (XRD, ICP-OES, N2 physisorption, TEM, UV–vis, FT-IR and XPS).